Effect of Institutional Support on Law Librarians’ Commitment in Southwest, Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This study investigates effect of institutional support on the commitment of law librarians in southwest, Nigeria. The specific motive for this paper is to examine the influence of institutional support on the commitment of law librarians in southwest, Nigeria. The descriptive survey research design was used for this study with the population of 49 law librarians in law libraries within South-West, Nigeria. Questionnaire was used as the research instrument to gather information from the respondents and one hypothesis was considered for the work at 5% level of significance; the result shown by the regression analysis was null. The study found a significant influence of institutional support on law librarians’ commitment in Southwest, Nigeria. Strong institutional support, in the form of financial resources, technical assistance and management encouragement, is associated with better commitment by law librarians’. The study concluded that institutional support, which includes financial support, technical support and management support, contributes significantly to the effectiveness and efficiency of law librarians’ commitment. The study recommended that Law library managements in Southwest, Nigeria should promote knowledge sharing and best practices within law libraries so as to learn from each other’s successes in providing institutional support.